Pemberdayaan Petani Melalui Digitalisasi Pertanian dan Penguatan Ekonomi Pedesaan di Kabupatenn Enrekang - Asrianto Asrianto; Amal Amal; Abdul Karim; Abd Kadir S; Sahrul Sahrul (Institut Teknologi dan Bisnis Semarang, 2026)
Digital transformation in the agricultural sector is one strategy to improve farmer welfare and strengthen the rural economy in the Society 5.0 era. Enrekang Regency has great potential as a horticulture and plantation center, but still faces various obstacles such as low digital literacy among farmers, limited access to market information, weak agricultural business records, and the suboptimal use of digital technology. This community service activity aims to increase farmer capacity through information technology-based agricultural digitalization supported by the Social and Environmental Responsibility (TJSL) Program of PT Pupuk Kalimantan Timur. The methods used include Participatory Rural Appraisal (PRA), training, mentoring, technology demonstrations, and monitoring and evaluation. A total of 60 farmers from several villages in Enrekang Regency participated in the program. The results of the activity showed an increase in farmers' ability to use digital agricultural applications, digital financial recording, social media, and marketplace-based marketing, and increased access to commodity price and weather information. This program also encouraged the formation of digital farmer groups that strengthen collaboration between farmers, local governments, universities, and the industrial sector. This activity has a positive impact on increasing productivity, farming efficiency, and strengthening the rural economy in a sustainable manner.